The effects of plasma from patients with active thyroid-associated orbitopathy on the survival and inflammation of melanoma-associated fibroblasts - Huifang Chen; Shiyuan Chen; Zhenfeng Liu (PeerJ)
Background Plasma from patients with active thyroid-associated orbitopathy (TAO-A) could cause inflammation to fibroblasts, and such a mechanism was explored in the context of melanoma. Methods Plasma samples collected from TAO-A patients and healthy control (HC) were primarily co-cultured with the melanoma-associated fibroblasts (MAFs) derived from melanoma patients. The survival and inflammation of the co-cultured MAFs were measured after confirming the levels of pro-inflammatory cytokines. Ki67 and Vimentin (VIM) markers were analyzed by immunofluorescence, and cell survival and migration were assessed using cell counting kit-8 (CCK-8) and Transwell. The THP-1 cells were induced to differentiate into macrophages, which were subsequently co-cultured to assess M1/M2 polarization status. Meanwhile, the levels of inflammatory factor were detected by enzyme-linked immunosorbent assay (ELISA). The gene expression was measured by reverse transcription quantitative PCR (RT-qPCR), and the activation of PI3K/AKT, STAT1, p65, and ERK signaling pathways was detected by Western Blot. Results Plasmas derived from TAO-A patients were characterized by elevated levels of pro-inflammatory cytokines, which enhanced the inflammation status and survival of MAFs, promoted the levels of PI3K and AKT, and downregulated expression of Bax. The co-culture of the plasma with MAFs evidently promoted M1 polarization and the phosphorylation of STAT1, P65 and ERK1/2. Conclusion These findings proved the effects of the plasmas of TAO-A patients on the survival and inflammation of MAFs, providing evidence for future studies to delve into the relevant mechanisms.